Can someone help please!!!!!
reza24 avatar

Answers

Answer 1
Answer:

Answer:

x

{x}^(2)  - 3


Related Questions

How is (s-t)(s/t) equivalent to (s^2/t) -s
Which shows one way to determine the factors of x3 – 9x2 + 5x – 45 by grouping?x2(x – 9) – 5(x – 9) x2(x + 9) – 5(x + 9) x(x2 + 5) – 9(x2 + 5) x(x2 – 5) – 9(x2 – 5)
Use the commutative and/or associative properties to simplify 9.731(4): 0.75. A) 7.29825 B) 38.925 C) 29.19375 D) 39.69375
How do you do this problem?You have $22 and you use it four tickets and after you bought it, you have $6 left. How much did each ticket cost?
X+2y+6=0Solve for the value of "y"And explain how to graph the result.

what is the first step in solving the quadratic equation x2 = ? take the square root of both sides of the equation. add to both sides of the equation. square both sides of the equation. subtract from both sides of the equation.

Answers

take the square root of both sides of the equation

Answer:

take the square root of both sides of the equation

Solve an equation to determine the unknown quantity.An emu that measures 30 inches in height is 75 inches less than 5 times the height of a kakapo.
What is the height of a kakapo in inches?

Answers

-75 times 5 = 30
Add 75 to 30 =105
105 divided by 5= 21
Kakapo should be 21 inches. Hope this helps sorry if wrong!

Simplify 5(MN + 1) - 5.

Answers

1. Distribute the 5 so that you get 5MN + 5 - 5.
Then you subtract the 5's and you're left with 5MN.

What is the next term in the sequence 7,12,17,22,...

Answers

27
Because there is a common difference of 5 (it is an arithmetic sequence)
27, because if you see the pattern, its adding 5 and 7 + 5=12 and 12+5=17 lastly 17+5=22 so when you add 22 plus 5 you get 26

The equation of line k is y=-1/5x -1/8. What is the equation of the line that is perpendicular to line k and passes through (0,0)?

Answers

y=-1/5 x-1/8
Gradient, m= -1/5
A line perpendicular will be;
m=15
y=mx+c
Replacing for x and y;
0=5(0)+c
c=0
y=5x

Two equations are given below:a − 3b = 4
a = b − 2

What is the solution to the set of equations in the form (a, b)?

(−2, −2)

(−3, −1)

(−9, −7)

(−5, −3)

Answers

Hello,

a-3b=4 (1)
a-b=-2 (2)

(1)-(2)==> -2b=6
=>b=-3 and a=-2+(-3)=-5

Answer D


Proof
-5+3=-2
-5-3(-3)=4



Other Questions